An effective uncertainty based framework for sustainable industrial product-service system transformation. (20th January 2019) - Erkoyuncu, John Ahmet; Roy, Rajkumar; Shehab, Essam; Durugbo, Christopher; Khan, Samir; Datta, Partha
Abstract: Industrial Product-Service Systems (IPS 2 ) can provide insights to enhance the environmental sustainability and lower environmental impact. However, its successful realisation for preventing the production of waste, while increasing efficiencies in the uses of energy and human capital remains a highly convoluted problem. This research article aims to address this issue by presenting an innovative uncertainty-based framework that can be used to assist in achieving increased sustainability within the context of IPS 2 . The developed framework explains the drivers for decision-making and cost to enable sustainability improvements in transforming to industrial services. This is based on academic literature, and multiple case studies of seven industrial companies with over 30 h of semi-structured interviews. The validation of the framework through two case studies demonstrates that uncertainty management can enable resource efficiency and offer sustainable transformation to service provision.